Influences of Outdoor Experiences During Childhood on Time Spent in Nature as an Adult - Debra K. Kellstedt, DrPH; Courtney S. Suess, PhD; Jay E. Maddock, PhD (Elsevier, 2024)
Introduction: Time spent in nature provides myriad physical and mental health benefits for both adults and children. Despite these benefits, most people spend too little time in nature to realize the maximal effect. Different types of childhood experiences may have differential influence on adult time in nature. This study assessed the influences of different kinds of childhood outdoor experiences on time spent in nature as an adult. The first aim was to utilize 20 childhood nature experience items to construct summative scales. The second aim was to examine the influence of each scale and other factors on adult time in nature. Methods: A 2-factor scale measuring wild and domesticated childhood nature experiences was developed using principal and confirmatory factor analyses. An online study of 2,109 American adults was conducted. Multiple linear regression examined the influences of the 2 childhood nature experiences scales, attitude and self-efficacy scales, and sex and age covariates on adult time spent in nature. Results: Significant predictors of adult time in nature were wild childhood nature experiences (β=0.279, p<0.001), positive attitudes about nature (β=0.12, p<0.05), negative attitudes about nature (β= −0.23, p<0.001), and self-efficacy (β=0.71, p<0.001). Conclusions: Wild childhood nature experiences (e.g., camping, hiking, and fishing) that include skill building, that are immersive and engaging, and that involve opportunity for social interaction may translate better into adult nature activities. Programs that introduce and support wild experiences may increase lifelong time spent in nature.